1995
DOI: 10.1108/02634509510088991
|View full text |Cite
|
Sign up to set email alerts
|

The impact of green product lines on the environment

Abstract: The literature examining the behaviour of environmentally conscious consumers has focused mainly on the examination of non‐product specific environmental knowledge and attitudes or environmental knowledge and attitudes in relation to single product lines. Employs the constructs of product‐line‐specific environmental knowledge and attitudes, that is knowledge of and attitudes towards the green products and their impact on the environment. Presents the results of an exploratory study examining the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 35 publications
0
70
0
Order By: Relevance
“…In reference to attitudes positive relationships have been identified in a number of cases (McGuiness et al, 1977;Kallgren and Wood 1986;Shrum and McCarty, 2001;Tilikidou and Delistavrou, 2004). There have been studies that followed suggestions by Ajzen and Fishbein (1977) and indicated that specific recycling attitudes are better correlated to recycling behavior than general social attitudes or general pro-environmental attitudes (Shrum et al, 1994;Martin and Simintiras, 1995;Balderjahn, 1988;Tilikidou, unpublished doctoral dissertation, p. 151). Davies et al (2002) found a positive association between attitudes and intention to recycling but intention was not found to be directly associated to behavior.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In reference to attitudes positive relationships have been identified in a number of cases (McGuiness et al, 1977;Kallgren and Wood 1986;Shrum and McCarty, 2001;Tilikidou and Delistavrou, 2004). There have been studies that followed suggestions by Ajzen and Fishbein (1977) and indicated that specific recycling attitudes are better correlated to recycling behavior than general social attitudes or general pro-environmental attitudes (Shrum et al, 1994;Martin and Simintiras, 1995;Balderjahn, 1988;Tilikidou, unpublished doctoral dissertation, p. 151). Davies et al (2002) found a positive association between attitudes and intention to recycling but intention was not found to be directly associated to behavior.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Past studies have revealed that environmental attitude was the direct predictor of pro-environmental intention and behaviour (Ellen, 1994;Roberts, 1996;Straughan and Roberts, 1999;Kim, 2002;Meinhold and Malkus, 2005;Milfont, 2007;Majláth, 2008;Lopez and Cuervo-Arango, 2008) and the green products purchase commitments are often based on environmental attitudes (Martin and Simintiras, 1995;Grunert and Juhl, 1995;Chan, 1996;Schlegelmich et al, 1996;Chan, K. 1999;Tanner and Kast, 2003;Kim and Choi, 2003;Fraj and Martinez, 2007;Tilikidou;. However, some of the researchers also commented that there is a gap between attitude and behaviour because the results of green purchases have often been disappointing (Maineiri et al, 1997;Peattie, 2001;Gupta and Ogden, 2006).…”
Section: General Attitude: Theoretical Concept and Empirical Studiesmentioning
confidence: 99%
“…After providing a brief review of the core theoretical issues (section 3), we will present a description of the experiment we 1 Hirschman (1970), for example, has divided consumer sanction power over corporate behaviour into three types: a positive sanction "loyalty", a negative sanction "exit" (terminating a business relationship) and "voice" (complaining or negative word-of-mouth). 2 See, for instance, Kinnear and Taylor (1973); Martin and Simintiras (1995); and Prothero and McDonagh (1993). 3 For a more thorough analysis of these methods, see Pearce and Turner (1990).…”
Section: Introductionmentioning
confidence: 99%